Effects of Extracellular pH Modulation on HIF-1α, c-Myc, and FOXO1 Expression in Colorectal Cancer Cells - Ibrahim, Sugeng; Putri Rifai, Fauziah Novita; Arda, Adzani Gaisani (Stem Cell and Cancer Research (SCCR), 2025)
Background: The tumor microenvironment (TME) of colorectal cancer (CRC) is characterized by an inverted pH gradient, with acidic extracellular and alkaline intracellular conditions that promote tumor progression and metabolic reprogramming. This altered pH landscape regulates key transcriptional drivers of glycolysis and proliferation, including hypoxia-inducible factor-1 alpha (HIF-1α), c-Myc, and the tumor suppressor Forkhead Box Protein O1 (FOXO1). Understanding how extracellular pH influences these regulators may provide new insights for pH-targeted cancer therapy. Methods: Human colorectal carcinoma HCT116 cells were cultured for 24 hours under six extracellular pH conditions (5.5–9.2). The expression of HIF-1α, c-Myc, and FOXO1 was quantified using quantitative real-time polymerase chain reaction (qPCR), and relative fold changes were analyzed by the 2^-ΔΔCt method. Results: Acidic conditions (pH 5.5–6.7) markedly upregulated HIF-1α and c-Myc while strongly suppressing FOXO1 expression. Conversely, mild alkalinity (pH 8.4) reversed this pattern, reducing HIF-1α and c-Myc while restoring FOXO1 expression, suggesting a transcriptional shift from glycolytic to oxidative metabolism. At higher alkalinity (pH 9.2), the expression of all three genes declined, indicating a threshold beyond which excessive pH elevation becomes detrimental to cellular regulation. Conclusion: Extracellular pH critically modulates metabolic gene expression in CRC cells. Acidic conditions activate glycolytic and oncogenic pathways via HIF-1α and c-Myc, while mild alkalinity suppresses these signals and reinstates tumor-suppressive FOXO1 activity. Controlled alkalinization of the TME may therefore represent a promising adjunctive approach to disrupt tumor metabolism and limit cancer progression.